Stormwater design for sustainable development - Rossmiller, Ronald Leroy (New York : McGraw-Hill Education, 2014)
'Complete coverage of managing stormwater runoff through sustainable design and development. Stormwater Design for Sustainable Development is an essential guide to the current practice of stormwater management in urban environments. When federal and state laws were passed addressing public concerns about nuisance and damaging flooding, water quality, and water resources, the responses included facilities crammed into developments as afterthoughts. This book offers ways to blend these efforts into neighborhoods, and commercial and industrial areas as natural features of them. Covers social, environmental, and economic concerns and issues Features numerous examples and land use plan views Contains detailed calculations for the design of best management practices for water quantity control and enhancement of water quality runoff Includes well-tested spreadsheets with all calculations for each step in the design process Reviews current regulations'--
Includes index.
Keywords: Urban runoff -- Management; Storm sewers; Drainage; Sustainable development